ANALISIS NILAI MORAL PADA PANTUN ADAT PERKAWINAN MASYARAKAT MELAYU KABUPATEN KARIMUN PROVINSI KEPULAUAN RIAU - Erni Erni; Supriyadi Supriyadi; Jusliani Jusliani (Perspektif Pendidikan dan Keguruan, 2014)
Pantun for Malay community in Kabupaten Karimun is a popular literary, for this reason the writers are interested to raise this problem by assigning the title "Analysis of Moral Values in Pantun at Malay Customary Marriage ofKabupaten Karimun Provinsi Kepulauan Riau ". The issues raised in this research is how the moral values inherent in traditional wedding rhyme Malay community Kabupaten Karimun Provinsi Kepulauan Riau. The purpose of this study was to obtain data information, systematically and in detail about the moral values inherent in traditional wedding rhyme Malay community at Kabupaten Karimun Provinsi Riau. The theory that the writers used to answer these problems was the theory of moral values related to responsibility, conscience and obligation to process the data. The sample in this study was limited to rhyme merisik meminang total 64 Pantun. The method which the writers usedwas descriptive method. Data collection techniques were observation and documentation. All the data that was analyzed found that 16 Pantun merisik in marriage customs Malay society Kabupaten Karimun Provinsi Kepulauan Riau, 1 Pantun moral value associated with responsibility, 11 Pantun moral value pertaining to the conscience, and 4 rhyme has moral values relating to liability. 48 Pantun in meminang in the marriage customs of Kabupaten Karimun Provinsi Kepulauan Riau, 12 Pantun moral value associated with responsibility, 27 Pantun moral value pertaining to the conscience, and 25 Pantun have moral values relating to liability